PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Jefri, Ulfi; Anggraeni, Anggi Nur; Amyati, Amyati (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to look at the effect of financial performance on stock returns in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The method used in this study is Associative with a quantitative approach. The research data used is secondary data obtained from the Company's financial statements that are the object of the research. The sampling technique uses the purposive sampling method. With a research population of 47 manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange for the 2018-2022 period and a sample of 9 companies with a research period of 5 years was obtained. With an analysis technique using SPSS Software Version 23. The results of the study show that the financial performance that is proximated using the Current Ratio, Debt to Equity Ratio partially has a negative and significant effect on Stock Returns, and the Return on Asset variable has a positive and significant effect on Stock Returns. Meanwhile, simultaneously and simultaneously that the Current Ratio, Debt to equity ratio and Return on Asset have a significant effect on the Return on Shares in manufacturing companies